Isolated Attosecond Pulse Generation without the Need to Stabilize the Carrier-Envelope Phase of Driving Lasers - Gilbertson, Steve; Khan, Sabih D.; Wu, Yi; Chini, Michael; Chang, Zenghu (My University, 2010)
Single isolated attosecond pulses can be extracted from a pulse train with an ultrafast gate in the generation target. By setting the gate width sufficiently narrow with the generalized double optical gating, we demonstrate that single isolated attosecond pulses can be generated with any arbitrary carrier-envelope phase value of the driving laser. The carrier-envelope phase only affects the photon flux, not the pulse duration or contrast. Our results show that isolated attosecond pulses can be generated using carrier-envelope phase unstabilized 23 fs pulses directly from chirped pulse amplifiers.